2018
DOI: 10.1002/elan.201700658
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Versatile Method for Determination of two Antihistamines in Association with Naphazoline Using Cathodically Pretreated Boron‐doped Diamond Electrode

Abstract: Antihistamines such as pheniramine (PHN) or chlorpheniramine (CPH) are commonly associated with naphazoline (NPZ) in eye drops and nasal decongestants. In this work, a batch‐injection analysis system with multiple pulse amperometric (BIA‐MPA) detection has been applied for the first time for fast simultaneous determination of naphazoline (NPZ) and pheniramine (PHN) or NPZ and chlorpheniramine (CPH). PHN or CPH was selectively detected at +1.1 V and both PHN and NPZ or CPH and NPZ were detected at +1.3 V using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
1
8
0
3
Order By: Relevance
“…The potential of BIA systems coupled to BDD electrodes and using multiple pulse amperometric (MPA) detection for simultaneous determinations was shown in the subsequent years. The BIA-MPA system was used successfully in the simultaneous determination of nimesulide and paracetamol (Pereira et al, 2013), codeine and diclofenac (Gimenes et al, 2013), propranolol and hydrochlorothiazide (Gimenes et al, 2014), diphenhydramine and 8-chlorotheophylline (dimenhydrinate) (Freitas et al, 2014), sulfamethoxazole and trimethoprim (Pereira et al, 2015), captopril and hydrochlorothiazide (Gimenes et al, 2015), amlodipine and atenolol (Silva et al, 2016), pheniramine and naphazoline (Oliveira et al, 2018b), or chlorpheniramine and naphazoline (Oliveira et al, 2018b). The possibility of selective determination of sildenafil (Garcia Cardozo et al, 2017) using the MPA technique was also recently shown.…”
Section: Bdd Electrode Coupled To Bia Systemsmentioning
confidence: 99%
“…The potential of BIA systems coupled to BDD electrodes and using multiple pulse amperometric (MPA) detection for simultaneous determinations was shown in the subsequent years. The BIA-MPA system was used successfully in the simultaneous determination of nimesulide and paracetamol (Pereira et al, 2013), codeine and diclofenac (Gimenes et al, 2013), propranolol and hydrochlorothiazide (Gimenes et al, 2014), diphenhydramine and 8-chlorotheophylline (dimenhydrinate) (Freitas et al, 2014), sulfamethoxazole and trimethoprim (Pereira et al, 2015), captopril and hydrochlorothiazide (Gimenes et al, 2015), amlodipine and atenolol (Silva et al, 2016), pheniramine and naphazoline (Oliveira et al, 2018b), or chlorpheniramine and naphazoline (Oliveira et al, 2018b). The possibility of selective determination of sildenafil (Garcia Cardozo et al, 2017) using the MPA technique was also recently shown.…”
Section: Bdd Electrode Coupled To Bia Systemsmentioning
confidence: 99%
“…Antihistamines such as pheniramine orchlorpheniramine are commonly associated with naphazoline (NPZ) in eye drops and nasal decongestants. Oliveira and coauthors develop a method for simultaneous detection of those compounds using batch‐injection analysis system with multiple pulse amperometric . BDD electrode was anodically pretreated by applying 0.01 A for 1000 s in 0.12 mol L −1 BR buffer solution and then cathodically pretreated by applying −0.01 A for 1000 s in a 0.1 mol L −1 H 2 SO 4 solution.…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%
“…Moreover, BP reports four official impurities; A, B, C and D. Literature review revealed that NPZ has been determined either in bulk powder or in presence with other drugs using several techniques including; spectrophotometry, [11][12][13][14][15][16][17][18][19][20] HPLC, [21][22][23][24][25][26][27][28][29][30][31][32] TLC 33 and capillary electrophoresis. [34][35][36][37][38][39][40] Pheniramine maleate (PHN) is an antihistaminic drug with anticholinergic properties. It binds to histamine H1 receptors, leading to inhibiting phospholipase A2, reducing cyclic GMP levels, and decreasing histamine.…”
Section: Introductionmentioning
confidence: 99%